PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASIONAL TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi pada SMAN 1 dan SMAN 2 Pekalongan) - 11.52.02.0125, Dyah Cipta Etikawati (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to analyze the influence of Organizational Culture and Leadership Style on Teacher Performance and Job Satisfaction as madiation variable.Object in this study is in SMAN 1 and SMA 2 Pekalongan by the number of respondents 105 respondents and the census method. Test used is the instrument and path analysis.Based on the results of the study can be summarized as follows: (1) Leadership positive and significant effect on job satisfaction, (2) Organizational Culture and significant positive effect on job satisfaction, (3) Leadership positive and significant impact on teacher performance, (4) Organizational culture positive and significant impact on teacher performance, (5) Job satisfaction and a significant positive effect on teacher performance , (6) Variable job satisfaction mediates the effect of leadership style on teacher performance , while the satisfaction variables keja not mediate the influence of organizational culture on teacher performance. Keywords: Leadership, Organizational Culture, Job Satisfaction, Teacher Performance